How do olivines record magmatic events? Insights from major and trace element zoning - de Maisonneuve, Caroline Bouvet (2017)
Reconciling the diverse records of magmatic events preserved by multiple crystals and minerals in the same sample is often challenging. In the case of basaltic–andesites from Volcán Llaima (Chile), Mg zoning in olivine is always simpler than Ca zoning in plagioclase. A model that explains a number of chemical patterns is that Llaima magmas stall in the upper crust, where they undergo decompression crystallization and form crystal-mush bodies. Frequent magma inputs from deeper reservoirs provide the potential for remobilization and eruption. The records of multiple recharge events in Llaima plagioclase versus an apparent maximum of one such event in coexisting olivine are addressed by using trace element zoning in olivine phenocrysts. We have integrated elements that (1) respond to changes in magma composition due to recharge or mixing (Mg, Fe, Ni, Mn, ±Ca), with (2) elements that are incorporated during rapid, disequilibrium crystal growth (P, Ti, Sc, V, Al). A more complex history is obtained when these elements are evaluated considering their partition coefficients, diffusivities, and crystal growth rates. The olivine archive can then be reconciled with the plagioclase archive of magma reservoir processes. Olivine (and plagioclase) phenocrysts may experience up to three or more recharge events between nucleation and eruption. Diffusion modeling of major and trace element zoning in two dimensions using a new lattice Boltzmann model suggests that recharge events occur on the order of months to a couple of years prior to eruption, whereas crystal residence times are more likely to be on the order of a few years to decades.